MEDIATIZATION OF ISLAMIC DA'WAH: VIRTUAL RELIGIOUS EXPRESSION, ALGORITHMIC AUTHORITY, AND THE DIGITAL RELIGIOUS CREDIBILITY CRISIS IN INDONESIA - Aldi Asy Syaikh Ar Rois; Siti Raudhatul Jannah; Kun Wasiz (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
Digital platforms have changed Islamic da'wah not only from the medium side, but also from the deepest structure. YouTube, Instagram, and TikTok are now the dominant spaces for religious communication in Indonesia reshaping the way Islam is expressed, authorized, and trusted by millions of digital Muslims. The study examines three interrelated dimensions: how digital platforms shape virtual religious expression; how algorithmic logic shifts religious authority from scholars and scholarly sanad to content creators and popularity metrics; and how the crisis of digital religious credibility arises when popularity replaces scientific competence in da'wah. Using a descriptive qualitative approach with critical discourse analysis, data were collected through digital observation of more than 150 da'wah content on three platforms, semi-structured interviews with seven deliberately selected informants, and documentation. The data analysis followed the interactive model of Miles, Huberman, and Saldana. The theoretical framework integrates Stig Hjarvard's theory of Religious Mediatization with the logic of Jose van Dijck's platform which includes algorithmicity, connectivity, popularity, and the economy of attention. These findings suggest that digital platforms impose a different grammar of religiosity that prioritizes spectacle, brevity, and emotional resonance over doctrinal depth. Algorithmic authority is progressively marginalizing scholars who do not adapt to the logic of the platform, while at the same time elevating da'i-influencers whose digital capital exceeds their scientific credentials. The result is a real crisis of credibility: Islamic knowledge is increasingly measured by the number of views and followers, not by sanad and scientific competence. This research contributes a new integrated analytical framework for the study of digital da'wah and provides practical implications for Islamic media literacy and da'wah communication ethics in the platform era.